Dysfunctional mitochondria, disrupted levels of reactive oxygen species, and autophagy in B cells from common variable immunodeficiency patients - Berman-Riu, Maria; Cunill, Vanesa; Clemente, Antonio; López-Gómez, Antonio; Pons, Jaime; Ferrer, Joana M. (Frontiers in Immunology, 2024)
Common Variable Immunodeficiency (CVID) patients are characterized by hypogammaglobulinemia and poor response to vaccination due to a deficient generation of memory and antibody secreting B cells. B lymphocytes are essential for the development of humoral immune responses and mitochondrial function, ROS production and autophagy are crucial for determining B cells fate. However, the role of those basic cell functions in the differentiation of human B cells remains poorly investigated. Here, we describe that naïve CD19+CD27- and memory CD19+CD27+ B cells subpopulations from healthy controls differ in terms of their dependence on these processes for their homeostasis, and demonstrate that different stimuli exert a preferential cell type dependent effect. We had previously found an increased susceptibility to activation-induced apoptosis and an imbalance in mitochondrial apoptosis regulation in memory B cells from a subgroup of CVID patients with a more compromised memory B cell compartment. In this paper, the evaluation of mitochondrial function, ROS production and autophagy in naïve and memory B cells from CVID patients disclosed subpopulation specific alterations. Dysfunctional mitochondria and autophagy were more prominent in unstimulated CVID CD19+CD27- and CD19+CD27+ B cells than in their healthy counterparts. Although naïve CD19+CD27- B from CVID patients had higher basal ROS levels than controls, their ROS increase after stimulation was lower, suggesting a disruption in ROS homeostasis. A failure in ROS cell signaling could impair CVID naïve B cell activation and differentiation to memory B cells. On the other hand, memory CD19+CD27+ B cells from CVID patients had both lower ROS basal levels and a diminished ROS production after stimulation with anti-B cell receptor (BCR) and IL-21. Decreased levels of ROS in CVID CD19+CD27+ B cells, which negatively correlate with their in vitro cell death and autophagy, could be detrimental and lead to their previously demonstrated premature death. The final consequence would be the failure to generate a functional B cell compartment in CVID patients.